The translation of Chinese poetry by Marcela de Juan - MI 宓田 Tian (Estudios de Traducción, 2017)
Marcela de Juan is an important translator, pioneer in the field of translation from Chinese into Spanish in the twentieth century, but there are few studies on her publications. Her translations of Chinese poetry stand out and are widely spread among Spanish readers. They constitute relevant material for researchers interested in the translation of Chinese poetry into Spanish.